Engaging Adults Experiencing Homelessness in Recovery Education: A Qualitative Analysis of Individual and Program Level Enabling Factors - Khan, Bushra M.; Reid, Nadine; Brown, Rebecca; Kozloff, Nicole; Stergiopoulos, Vicky (Frontiers in Psychiatry, 2020)
Abstract Purpose Recovery Education Centres (REC) in mental health offer a new model of providing recovery supports through emancipatory adult education and recovery-oriented service principles. Despite the widespread adoption of RECs, there is limited evidence regarding key programmatic features, particularly for unique subpopulations or service delivery contexts. Methods The Supporting Transitions and Recovery Learning Centre (STAR) in Toronto, Ontario is the first REC in Canada and one of few worldwide supporting adults transitioning out of homelessness. Qualitative methods were used to explore the experiences of 20 participants through semi-structured interviews exploring participants' experiences of REC participation and perceived key program features. Interviews were conducted between July 2017 and June 2018, six to 14 months following REC enrollment, were audio-recorded, transcribed verbatim and analyzed using inductive thematic analysis. Results In contrast to past experiences with health and social services, participants described a welcoming and respectful physical and interpersonal environment with low-barrier seamless access facilitating their engagement and participation. Although the realities of homelessness presented barriers for some, participants described that the involvement of peers, as role models, and the self-directed, strengths and skills-based curriculum, co-produced and co-delivered by peers and professionals, were instrumental in activating the process of recovery. Conclusions / Implications Findings are consistent with the growing evidence base of the defining features of RECs and suggest this model can be successfully extended to support recovery among adults transitioning out of homelessness. This unique examination of Canada’s first REC for adults exiting homelessness can help guide program and policy development to better support this disadvantaged population.